Integration of EMI (English as Medium of Instruction) through a collaborative teaching scheme to improve the quality of teachers - Affandi, Akhmad; Fadlih, Andi Muhammad; Nastah, Mardiyanah; Fakhri , M. Miftach; Mursalim, Muliana (Panrannuangku Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to improve teachers' ability to implement Collaborative Teaching based on English Medium Instruction (EMI) at SMA Negeri 5 Gowa. The program was carried out using a Participatory Action Research (PAR) approach involving 23 teachers from various subjects. The instrument was in the form of a pre-posttest questionnaire with 20 Likert scale statements (1–5) which included four dimensions: EMI ability, understanding collaborative teaching, collaborative implementation of collaboration, and effectiveness and feedback. The results of the analysis showed a significant increase with an average of +1.27 points in all dimensions. The biggest improvement was in the aspect of collaboration implementation (+1.29), particularly the skill of designing a 20-minute micro-lesson and providing clear collaborative instructions. These findings confirm that the EMI-based Collaborative Teaching Scheme is able to strengthen teacher confidence, increase pedagogical understanding, and foster a peer-mentoring culture in schools. The use of PAR as a framework of service has proven to be effective because it places teachers as active partners in the planning, implementation, and reflection process. The program not only improves short-term skills, but also forms an ecosystem of continuous reflective learning. Thus, this model has the potential to be replicated in other secondary schools as a strategy to improve the quality of education that is in line with the Impact Campus policy and SDGs targets